Cytokine Profile in the Prognosis of Coronary Heart Disease Comorbidity in Chronic Obstructive Pulmonary Disease (Eurasian Medical Research Periodical, 2023)
The objective of the to determine the relationship between cytokine levels and the clinical course of CHD with COPD.